Sondologics : product diversion and MAP violations in internet channels - Coughlan, Anne T. (London : Kellogg School of Management, 2016)
Sondologics, a manufacturer of video, audio, and gaming accessories products, was experiencing pricing and distribution problems in its channels. Numerous retailers were complaining about unfair price competition from unauthorized retailers, i.e., gray marketers, on standalone websites or Amazon's Marketplace, offering discounts of up to 30% off list price. The company estimated that about 10% of its retail volume in the United States was being generated by unauthorized retailers. Compounding the problem, gray marketers and authorized retailers alike were selling at below-list prices, which violated the Sondologics MAP (minimum advertised pricing) policy. Sondologics was considering numerous initiatives to address the MAP and gray-market problems, including retaining a third-party service to monitor pricing and distribution in the channel. Students are asked to develop recommendations that would promote sales while protecting the name-brand image and price points of Sondologics' products.
Originally published in Coughlan, A. T. (2016). Sondologics: Product diversion and MAP violations in internet channels. 5-416-753. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sondologics; Price cutting; Gray market; Electronic commerce